2021
DOI: 10.3389/fmed.2021.786414
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anticoagulation Treatment in COVID-19 Patient Subgroups Identified by Clinical-Based Stratification and Unsupervised Machine Learning: A Matched Cohort Study

Abstract: Objective: To explore the efficacy of anticoagulation in improving outcomes and safety of Coronavirus disease 2019 (COVID-19) patients in subgroups identified by clinical-based stratification and unsupervised machine learning.Methods: This single-center retrospective cohort study unselectively reviewed 2,272 patients with COVID-19 admitted to the Tongji Hospital between Jan 25 and Mar 23, 2020. The association between AC treatment and outcomes was investigated in the propensity score (PS) matched cohort and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Given the remarkable contribution of coagulopathy in the pathogenesis of COVID-19 ( 108 ), anticoagulation therapy is anticipated to benefit patients with severe COVID-19. In this context, a single-center retrospective cohort study investigated the efficacy of anticoagulation therapy in patients with COVID-19, revealing that anticoagulation therapy was associated with lower in-hospital mortality in critically ill patients with COVID-19; however, unsupervised machine learning analysis revealed that the subgroup of patients with multiorgan dysfunction and excessive inflammation might not benefit from anticoagulation therapy ( 109 ).…”
Section: Subphenotypes and Endotypes Of Covid-19mentioning
confidence: 99%
“…Given the remarkable contribution of coagulopathy in the pathogenesis of COVID-19 ( 108 ), anticoagulation therapy is anticipated to benefit patients with severe COVID-19. In this context, a single-center retrospective cohort study investigated the efficacy of anticoagulation therapy in patients with COVID-19, revealing that anticoagulation therapy was associated with lower in-hospital mortality in critically ill patients with COVID-19; however, unsupervised machine learning analysis revealed that the subgroup of patients with multiorgan dysfunction and excessive inflammation might not benefit from anticoagulation therapy ( 109 ).…”
Section: Subphenotypes and Endotypes Of Covid-19mentioning
confidence: 99%
“…Cluster analysis and other data-driven methods may help distinguish people who are most likely to benefit from health interventions and those who do not get any benefit [ 9 , 10 ]. Therefore, in this study, we used cluster analysis to distinguish different groups of patients eligible for outpatient cardiac rehabilitation based on several characteristics, and we compared outcomes between the groups.…”
Section: Introductionmentioning
confidence: 99%